Assessment of a probiotic based on Bacillus subtilis and its endospores in the obtainment of healthy lungs of pigs - Ayala, L?zara; Bocourt, Ram?n; Mili?n, Grethel; Castro, Manuel; Herrera, Magaly; Guzm?n, Juan Alberto (Cuban Journal of Agricultural Science, 2012)
In order to assess the effect of a probiotic based on Bacillus subtilis and its endospores on the obtainment of healthy lungs of pigs, 76 prefattening animals of 21 kg of average weight were slaughtered according to completely randomized design. Three groups were formed considering the descendent of the sows consuming the probiotic in the final gestation stage (21 and 30 d before the farrow) (1), during lactation (2) and post-weaning stage (3), at a rate of 109 endospores/g of concentrate. The hemoglobin, hematocrit and relative weight of the thymus and spleen were determined to 24 animals. The hematological indicators of hemoglobin and hematocrit were within the normal range for the category and animal species. The relative weight of the thymus (0.08 vs. 0.09 vs. 0.08) only differed (P < 0.05) in group 2. However, the weight of the spleen (0.18 vs1.50 vs. 1.62) was superior in the animals consuming the probiotic. The percentage of obtainment of healthy lungs was superior (P < 0.01) in the pigs receiving the product. The lungs, in the groups 2 and 3, increased in 35 and 33 percent units, respectively, in respect to the control. It is concluded that the consumption of the probiotic by the pregnant sow and the descendents favors the obtainment of healthy lungs. Extending these results to a higher number of pigs for the production of healthy lungs is recommended. Key words: pigs, healthy lungs, probiotic, Bacillus subtilis, endospores.